The Effect of Learning Climate, Organizational Support, and Supervision on the Performance of Lecturers - Jopinus Saragih (International Journal of Economics (IJEC), 2022)
This study is: to analyze the effect of learning climate on the performance of lecturers at Efarina University, to analyze the effect of organizational support on the performance of lecturers at Efarina University. Analyzing the effect of supervision on the performance of Lecturers at Efarina University, Analyzing the influence of the learning climate, organizational support and supervision simultaneously with the performance of Lecturers at Efarina University. The location or place of research is at Efarina University . In this research activity, data and information were collected using the following methods: Questionnaire given to Efarina University lecturers who became respondents . Simultaneous testing shows that the climate variables learning , support organization work , and supervision have a positive and significant effect on the performance of Efarina University lecturers. Partially, the learning climate has a positive and significant effect on the work performance of Efarina University lecturers. Partially organizational support has a positive and significant effect on the work performance of Efarina University Lecturers, Partially supervision does not significantly affect the work performance of Lecturers at Efarina University, the R2 value obtained is 0.423 or 42.3% which indicates the ability of the climate variable learning , support organization and supervision in explaining the variation that occurs in the Lecturer 's performance variable is 42.3%, while the remaining 57.7% is explained by other variables that are not included in the model such as compensation, organizational culture, job satisfaction, and others.